PROBLEMATIKA PEMBELAJARAN BAHASA ARAB MASA PANDEMI COVID-19 DI MIN 1 KOTAWARINGAIN TIMUR - Mukrandi Mukrandi (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2020)
Coronavirus disease 2019 (Covid-19) is currently a world health problem, as well as in the world of education. This study aims to analyze the problems faced by Arabic language teachers in learning during the Covid-19 pandemic at MIN 1, East Kotawaringain and how teachers' strategies are in overcoming these problems. This research uses a qualitative approach, with a descriptive qualitative type. The research site was in MIN 1 East Kotawaringain, the research subjects were Arabic teachers and the informants were the school principal and grade VI students at MIN 1 Kotawaringain Timur. The results of the study are: 1) The problem of learning Arabic originates from internal and external factors, internal factors, namely attention, interest, motivation and students' readiness to accept learning with new concepts. Meanwhile, external factors include family, school and community aspects. 2) The solution to the problem of learning Arabic is to focus on problems that arise from the dimensions of students, namely by giving gifts to overcome the lack of interest in learning and student motivation and providing free quotas for students who really need to solve the problem of the learning costs incurred. students then for the problem of student difficulties because there is no assistance provided by parents, the school provides technical guidance and mentoring for students.